PENERAPAN GOOD DAIRY FARMING PRACTICES (GDFP) DAN DAMPAKNYA TERHADAP KUALITAS SUSU DI REMBANGAN DAIRY FARM - Septian Pawulan Catur Lestari; Ahmad Humaidi Kamil; Ani Sulistyawati Ramli; Iis Nur Asyiah; Imam Mudakir (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The implementation of Good Dairy Farming Practices (GDFP) is an important component in ensuring the quality and safety of fresh milk produced by dairy farms. This study aims to analyze the implementation of GDFP at Rembangan Dairy Farm Jember and evaluate its impact on the quality of milk produced. The research method used a quantitative descriptive approach through field observations, structured interviews, and laboratory analysis of milk quality parameters, including total plate count (TPC), fat, protein, solids-not-fat (SNF), pH, and hygiene levels during the milking process. The results showed that most GDFP indicators have been implemented well, especially in aspects of animal health management, barn sanitation, and milking procedures. Consistent implementation of GDFP contributed to the achievement of milk quality with TPC values within the national standard limits, and fat, protein, and SNF levels that meet SNI 3141.1: 2011. However, improvements are still needed in aspects of feed management and cow stress control to optimize productivity and milk quality stability. Overall, the implementation of GDFP at Rembangan Dairy Farm has had a positive impact on milk quality and can serve as a model for implementing sustainable dairy farming practices.